Synthesis and Characterization of Coordination Compounds of Silver(I) Nitrite with Ligands Ethylenethiourea and N,N'-diethylthiourea - Fariati Fariati; Nurul Istikfaroh; Effendy Effendy; Lutfia Ayu Darojah (The Journal of Pure and Applied Chemistry Research, 2016)
Silver(I) nitrate and ethylenethiourea (etu) in 1 : 4 stochiometry have been reported [1]. Coordination compounds of A and B as silver(I) nitrite with etu and silver(I) nitrite with N,N’-diethylthiourea (detu) respectively, have never been done. The purposes of this study are to synthesize and characterize coordination compounds of A and B. Synthesis coordination compound of A with 1 : 4, while B with 1 : 2 stoichiometry. Both of coordination compounds are conducted directly in acetonitrile. Compounds obtained are characterized by melting point, electrical conductivity measurement, SEM-EDX, qualitative nitrite test, free energy calculation and structures prediction using Spartan’14 v1.1.0. Coordination compounds of A and B are colourless needle and prism crystals; have melting point of 189°C and 103-105°C; free energy of -289,2567 and -1182.8101 kJ/mol respectively. Electrical conductivity measurement and qualitative nitrite test show that the obtained compound of A is an ionic and B is a molecular one. EDX analysis gives empirical formula prediction of two coordination compound A is C12H24AgN9O2S4  and  B is C15H36AgN7O2S3.